The HER2 amplicon includes several genes required for the growth and survival of HER2 positive breast cancer cells — A data description - Hongisto, Vesa (Genom Data, 2014)
A large number of breast cancers are characterized by amplification and overexpression of the chromosome segment surrounding the HER2 (ERBB2) oncogene. As the HER2 amplicon at 17q12 contains multiple genes, we have systematically explored the role of the HER2 co-amplified genes in breast cancer cell growth and their relation to trastuzumab resistance. We integrated array comparative genomic hybridization (aCGH) data of the HER2 amplicon from 71 HER2 positive breast tumors and 10 cell lines with systematic functional RNA interference analysis of 23 core amplicon genes with several phenotypic endpoints in a panel of trastuzumab responding and non-responding HER2 positive breast cancer cells. In this Data in Brief we give a detailed description of the experimental procedures and the data analysis methods used in the study (1).